(untitled) (Sains Humanika, 2017)
In the development of a society and a nation-state, the aspect of leadership plays a key role. Moreover, the leadership comes from the figures who are called ulama’ or Muslim scholars. Kiai Haji Ahmad Shah is a renowned scholar in Johor. He served as Cadi or an Islamic Judge in several districts in Johor before being appointed Chief Islamic Judge of Johor. He was born in 1901 in Kampung Rimba Terjun, Pontian, Johor. His excellence in mastering various fields of knowledge and the talent of leadership began since childhood. His personal excellence attracted the public to explore the teachings of Islam, and he became a role model to amny leaders as well as murabbi or educators of today. The persistence of Kiai Haji Ahmad Shah in facing the challenge of developing and strengthening the faith of Muslims in the era before independence were the main focus of this study. This also shows the Islamic leadership in Kiai Haji Ahmad Shah; a leader who really believes in the "Leadership by Example"